James Knight and Walter C. White papers - Knight, James, 1787-1858.; White, Walter C., -1837.
Correspondence and financial, legal, and real estate papers relating chiefly to the real estate and business partnership of James Knight and Walter C. White in Fort Bend County, Texas. Includes a hand drawn map of the county showing plots of land with names of their owners.
"Old Three Hundred" colonists and land grantees from Stephen F. Austin's colony in Texas.
Collection material in English and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Austin, Stephen F. -- 1793-1836.; Landowners -- Texas -- Fort Bend County -- Maps; Pioneers -- Texas -- Fort Bend County; Real property -- Texas -- Fort Bend County; Real property -- Texas -- Fort Bend County -- Maps; Fort Bend County (Tex.) -- Commerce; Fort Bend County (Tex.) -- History; Fort Bend County (Tex.) -- Maps; Texas -- Commerce; Texas -- History -- To 1846.; Colonists